2019
DOI: 10.1111/jmcb.12609
|View full text |Cite
|
Sign up to set email alerts
|

Inflation‐Indexed Bonds and Nominal Bonds: Financial Innovation and Precautionary Motives

Abstract: This paper introduces a two-period monetary general equilibrium model with proportional transaction costs on nominal and inflation-indexed bonds. This paper demonstrates that financial innovation on indexed bonds causes equilibrium interest rates of the nominal bond to increase when agents have precautionary saving motives. This result implies that ignoring precautionary motives would underestimate savers' welfare gain and overestimate borrowers' welfare gain from innovation on indexed bonds.JEL codes: D52, E4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For example, Magill and Quinzii (1997) assume that inflation volatility is from monetary shocks while Geanakoplos (2005) assumes that it is from intrinsic endowment shocks. In a general equilibrium model under unstable monetary policy, Kang (2020) showed that indexed bonds do not necessarily lead to Pareto-improvement.…”
Section: Notesmentioning
confidence: 99%
“…For example, Magill and Quinzii (1997) assume that inflation volatility is from monetary shocks while Geanakoplos (2005) assumes that it is from intrinsic endowment shocks. In a general equilibrium model under unstable monetary policy, Kang (2020) showed that indexed bonds do not necessarily lead to Pareto-improvement.…”
Section: Notesmentioning
confidence: 99%
“…An indexed bond is a bond whose coupon is linked to the price of an underlying (Kang, 2020). Indexed-green bond refers to green bonds linked to the price of another asset (Hassani & Bahini, 2022).…”
mentioning
confidence: 99%